A complete and strongly anonymous leximin relation on infinite streams - Geir B. Asheim; Stéphane Zuber (Center for Economic Studies and ifo Institute (CESifo), 2011)
Various extensions of the leximin order to the infinite dimensional setting have been suggested. They relax completeness and strong anonymity. Instead, by removing sensitivity to generations at infinite rank this paper defines a complete and strongly anonymous leximin relation on infinite streams. The order is axiomatized, and it is shown to be the limit of extended rank-discounted utilitarianism for any utility function, as the discount factor approaches zero.
Keywords: D63; D71; 330; intergenerational equity; lexicographic maximin